(untitled) (International Journal of Language, Literacy and Translation, 2025)
This paper focuses on the English translation of Xi Jinping’s political discourse. This translation is not only a key component of China’s external publicity efforts but also embodies Xi Jinping’s diplomatic narrative style and the diplomatic thought of socialism with Chinese characteristics for a new era, the latter of which mainly refers to the diplomatic policies and principles advocated by the current Chinese government under the leadership of Xi Jinping. By applying Mona Baker’s (2018) narrative theory, this paper aims to investigate whether and how the translation of Xi Jinping’s political discourse embodies these four core narrative features—temporality, relationality, causal emplotment, and selective appropriation—through textual analysis. It is found that the translation of Xi Jinping’s political discourse clearly manifests these four core narrative features. This not only highlights the key role and the effectiveness of the translator as the subject of translation but also provides strong support for the construction of China’s diplomatic narratives. Therefore, the narrative theory of translation has significant applicability to the translation and research of political discourse, offering a powerful analytical tool for this field.